2022
DOI: 10.1017/gmh.2022.10
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural exploration of compassion, and facilitators and inhibitors of compassion in UK and Sri Lankan people

Abstract: Background Practising compassion has shown to increase well-being and reduce distress in people across cultures. However, very little research has explored cultural differences in different facets of compassion with a dearth of research evident especially in the Asian context. Several inhibitors and facilitators of compassion have been identified although the nuances of cultural differences of these remain unexploited. This study aimed to discover cross-cultural similarities and differences of the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Therefore, it seems fair to propose that the CEAS may be a more appropriate measure of compassion. However, none of the papers included in this meta-analysis used the CEAS, although other recent research using this measure in Asian countries such as Japan (Asano et al, 2020) and Sri Lanka (Kariyawasam et al, 2021(Kariyawasam et al, , 2022 have emphasised the advantages of using this measure (Asano et al, 2020). Thus, it would be useful for future research to investigate the effectiveness of compassion-based interventions using the CEAS in Asian communities to further understand the interplay between the three flows of compassion and well-being.…”
Section: Discussion Compassion-based Interventions On Self-compassionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it seems fair to propose that the CEAS may be a more appropriate measure of compassion. However, none of the papers included in this meta-analysis used the CEAS, although other recent research using this measure in Asian countries such as Japan (Asano et al, 2020) and Sri Lanka (Kariyawasam et al, 2021(Kariyawasam et al, , 2022 have emphasised the advantages of using this measure (Asano et al, 2020). Thus, it would be useful for future research to investigate the effectiveness of compassion-based interventions using the CEAS in Asian communities to further understand the interplay between the three flows of compassion and well-being.…”
Section: Discussion Compassion-based Interventions On Self-compassionmentioning
confidence: 99%
“…Huang et al, 2021 ; Tung, 2020 ) were found to be effective in increasing self‐compassion and well‐being and in reducing negative affect in Asian communities. Given that many people from Asian backgrounds do not seek help for their emotional well‐being due to high shame and criticism, stigma and other help‐seeking barriers in their societies (Kariyawasam et al, 2022 ; Mak et al, 2019 ), it seems fair to propose that online interventions such as the Self‐Compassion App (Beaumont & Irons, 2021 ) maybe more appropriate for people in Asian communities. This would also reduce the need and cost of training clinicians or other specialist staff to deliver compassion‐based approaches in cultures where there are high levels of poverty and limited funding for mental health clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation